A Study On The Stock Market's Reaction To Dividend Announcements - Kharel, Milan (My University, 2009)
This study investigates the stock market’s reaction to the dividend announcement in the Helsinki stock market using event study approach. The sample includes the most active shares of Helsinki Stock exchange. Daily stock prices and daily stock indices during the window period from the year 2005 to 2009 have been examined. MAAR and CAR values have been calculated and analyzed. Several potential explanations and signaling hypothesis and information content hypothesis propose that dividends represent favorable signals about the future prospects of firms. However, the empirical results show that dividend payment does not signal any information to the investors, so Investors do not gain value from the dividend announcements. It has been found that market adjusted abnormal returns are very close to zero which is consistent with the set null hypothesis and there is no reaction of stock market to the dividend announcements in the Helsinki stock market. Furthermore, it supports the dividend irrelevancy theory.
Keywords: Dividend announcement; MAAR; CAR; Market reaction; fi=Finance and Accounting|; fi=Master's Degree Programme in Finance|